1997
DOI: 10.1016/s0022-5347(01)64698-6
|View full text |Cite
|
Sign up to set email alerts
|

Electroejaculation Versus Vibratory Stimulation in Spinal Cord Injured Men: Sperm Quality and Patient Preference

Abstract: There was a slight advantage in sperm quality and a high patient preference in favor of penile vibratory stimulation. Penile vibratory stimulation should be attempted first to induce ejaculation in spinal cord injured men, with electroejaculation reserved for failures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
1
12

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(90 citation statements)
references
References 9 publications
1
75
1
12
Order By: Relevance
“…4 ± 6,20 Compared to the alternative treatment of electroejaculation, PVS is less invasive, is preferred more by patients, 21 and results in better semen quality. 21,22 PVS, however, is not successful in all patients, and there are currently no established guidelines for selecting patients for this method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 ± 6,20 Compared to the alternative treatment of electroejaculation, PVS is less invasive, is preferred more by patients, 21 and results in better semen quality. 21,22 PVS, however, is not successful in all patients, and there are currently no established guidelines for selecting patients for this method.…”
Section: Discussionmentioning
confidence: 99%
“…4 ± 6,20 Compared to the alternative treatment of electroejaculation, PVS is less invasive, is preferred more by patients, 21 and results in better semen quality. 21,22 PVS, however, is not successful in all patients, and there are currently no established guidelines for selecting patients for this method. While previous studies have shown that higher success rates of ejaculation are obtained with high compared to low levels of injury, 4,23 and high compared to low amplitude vibration, 4,13 these parameters are not completely predictive of ejaculation.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9] In our previous study, by using EEJ combined with assisted reproductive technique (ART), we showed high percentage of pregnancies despite the typically poor sperm motility. 10 In cases where azoospermia was evident during initial evaluation, the only option to conceive was to perform testicular biopsy for sperm retrieval and IVF.…”
Section: Introductionmentioning
confidence: 99%
“…Both of these techniques are far more invasive than PVS and generally result in fewer motile sperm. 15 In EEJ, electricity is delivered through a rectal probe to induce ejaculation, which always requires administration by a doctor. Furthermore, SCI men with incomplete lesions and/or preserved pelvic sensation may require general anesthesia.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to PVS, in which the vast majority of patients have mainly antegrade ejaculation, EEJ often results in some degree of retrograde ejaculation, which must then be collected from the bladder by cathetrization after EEJ. 15 Surgical sperm retrieval, which may involve testicular biopsies and/ or needle aspiration of sperm from the testis or epididymis 16 are invasive procedures that may result in a variety of adverse events including bleeding, infection and prolonged testicular pain. Furthermore, the numbers of sperm obtained from surgical sperm retrieval procedures are usually so low that it commits the couple to higher levels of ART such as IVF/ICSI.…”
Section: Resultsmentioning
confidence: 99%